The impact of stance during heel raises on the hybrid ultimate lifting kit (HULK) device: A future microgravity exercise machine - Kluis, Logan; Patel, Ravi; Thompson, William K.; Lewandowski, Beth; Diaz-Artiles, Ana (Frontiers in Physiology, 2022)
Extended missions in microgravity, such as those on the International Space Station (ISS) or future missions to Mars, can result in the physiological deconditioning of astronauts. Current mitigation strategies include a regimented diet in addition to resistance training paired with aerobic exercise. With the increased effort toward long duration space missions, there is room to optimize the cost, required time of use, and mass of exercise equipment. This research effort focuses on understanding the biomechanics of Heel Raise (HR) exercises while using the Hybrid Ultimate Lifting Kit (HULK) device, an exercise device designed to optimize volume and functionality. Using the biomechanics tool OpenSim, the effect of HR foot stance (15 degrees inward, 15 degrees outward, and straight) was assessed by analyzing kinematic and kinetic data. In particular, we analyzed peak joint angles, range of motion, joint moments, and angular impulses of a single subject. Preliminary results indicated no significant differences in terms of ankle/metatarsophalangeal/subtalar joint angles, range of motion, joint moments, and angular impulses between foot stances. In addition, loaded HR exercises were compared to body weight HR exercises without the HULK device. Finally, recommendations are made towards an optimal HR routine for long-duration space missions. The impact to health and rehabilitation on Earth is also discussed.